ed in words are called word
oth word for applied pro
Example 6. Soloe 3(x - 2) = 2(x + 1) - 3.
Solution. Here we should remove the brackets first.
3(x - 2) - 2(x + 1) - 3
3r - 6 = 2x + 2-3
3x = 2x + 2-3 + 6
3x = 2x + 5
3x-2x = 5
x = 5.
USES OF LI
word problems
Problems stated in
Success with wo
involves two ste
Second, solving
(transposing -6 from
6 from
olving word problems
Solving we
(transposing 2x from
wide variety of word to
all problems. However,
a the statement of the pro
linear equation in on
NOTE
From the above examples, we observe that every linear
has exactly one solution.
Due to the wide
works in all probl
Read the
found
Represent the
Determine w
Solve the res
Example 1.15
Solution. Le
128 - 58² 4 mx 7 is
Example 7. Find the value of m if the value of the expression 23
when x = -1.
Solution. Given, the value of 2x - 5x2 + mx - 7 is 10 when
.: 21-1) - 5 (-1)2 + (-1)- 7 = 10
= -2-5-m-7 = 10 -14 - m = 10
= -m= 10 + 14 m = 24 m = -24.
I
5 added to to
Exercise 6.1
1 Solve each of the following equations:
(1) x + 6=8
(11) 2-x=5
(iii) 4x = -6
(id) 7 = 5 (2) 24-3=2
(vi) 4 - 5y = 2
2. Solve the following equations:
(1) 5(x + 1) = 25 (11) 2(3x - 1) = 10 (ii) 37 -1 = 11
3. Solve the following equations:
(1) 5x - 6 = 12 - x (in) 11 + 1 =4-n (in) 5p + 7 = 19 - 22
(iv) 2x + 1 - (0)5 -4 (vi) 18 - 24 = 11 + y.
4. Solve the following equations and verify your answers:
(1) 3 (x + 7) = 18
at the unknown quan
mine which expressions
e the resulting equation
te 1.1f 5 is added to tunica
tion. Let the required mus
ice the number 23,
Aded to twice the numi
cording to the problem
2x + 5 = 29
2x = 29 -5 = 2
Hence, the required nus
Example 2. If thrice a certa
Find the number.
ution. Let the requin
Thrice the number =
Thrice the number
9 more than the nu
According to the p
3x - 7 = x
3x-X=9
Hence, the requir
5
(in) 2 (x - 1) = x + 2
(iv) 4(2x - 1)-2(x-5) = 5(x + 1) + 3
5. Find the value of p if the value of 4 - 3x - px - 5 is equal to 23 when x = -2
Example 3. One-fo
number.
Solution. Let the
Its succeeding
According to
(ii) 3r - 1 = 2 *-) + 5
5x -
Answers
Answered by
16
Answer:
Step-by-step explanation:
Example 2: The coefficient of xy in 3x2 zy + 7xyz – 2z2x is
(a) 3z (b) – 2 (c) 7yz (d) 7z
Solution: Correct answer is (d).
Example 3: The factors of the term –xy2 are
(a) x × y × y (b) – 1 × y × y
(c) – 1 × x × y (d) – 1 × x × y × y
Solution: Correct answer is (d).
In Examples 4 to 7, fill in the blanks to make the statements true.
Answered by
26
(2x−1)(x−3)=(x+5)(x−1)
Similar questions
Math,
6 months ago
Social Sciences,
6 months ago
Science,
6 months ago
Math,
1 year ago
Chemistry,
1 year ago